KEPENTINGAN QATAR KELUAR DARI KEANGGOTAAN ORGANIZATION OF THE PETROLEUM EXPORTING COUNTRIES (OPEC) TAHUN 2019 - Hartalis "; Indra Pahlawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study explains about Qatar's withdrawal from OPEC membership. Qatar joined OPEC in 1961. Qatar is a small producer in OPEC. Qatar produces 601.000 barrels per day and contributes 2% of OPEC's total output. Qatar is the first GCC country to leave OPEC. The source of this research was obtained through literature reviews, books, websites, and others. The source of analysis is qualitative method. This study uses the perspective of liberalism, the level of analysis of the nation state, this research based on foreign policy theory and the concept of national interest in analyzing research. On 3 December 2018, the Secretary General of OPEC, Mohammed. S Barkindo, received a letter from Qatar expressing its desire to withdraw from OPEC pursuant to Article 8 of the FAO Statute. Qatar's decision to withdraw from OPEC to increase its role internationally as well as its long-term strategic plan. The geo-political context of Qatar's decision is mostly related to the behavior of marginalization of Saudi Arabia within OPEC, through coordination with Russia and Donald Trump's pressure on OPEC.   Keywords: OPEC, LNG, PETROLEUM, GEOPOLITIC.